Evaluation of Anti-Helicobacter pylori Antibodies in A group of Iraqi Patients with Atherosclerosis and Coronary Artery Disease (Iraqi Journal of Science, 2023)
Evaluation of Anti-Helicobacter pylori Antibodies in A group of Iraqi Patients with Atherosclerosis and Coronary Artery Disease